NILAI-NILAI FILOSOFIS MASYARAKAT JAWA DALAM KONTEKS PENDIDIKAN KARAKTER DI ERA MILENIAL - Ahmad Muslich (Universitas Muhammadiyah Ponorogo, 2018)
Every nation in this world must have noble values that become the philosophical basis and give direction and purpose in nation, state, society and run a government. These noble values are derived from religious teachings and values that are believed to be true by the society in which values are carried out. The Indonesian nation is a State that integrates the various tribes, cultures, races, customs that are in it. One of them is Javanese culture. As a tribe with a population of a lot of marriages, there are so many philosophical values that are used as guidance for all people and government in this country. Even many of the values of philosophy both in purpose and reality are still very relevant to become the characters of this nation's children in the midst of the millennial era.